PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODA 2008-2012 - Yuliarni, Resti; Kurniawati, Indah (Universitas Ahmad Dahlan, 2014)
The purpose of this study was to determine how the effect of financial performance on the disclosure of corporate social responsibility (CSR). In this study the company's financial performance is measured using return on asset (ROA), net profit margin (NPM), current ratio (CR), debt to equity ratio (DER), and inventory turnover (INTO). The sample used is secondary data from the Indonesia Stock Exchange (IDX) Annual Report ie companies listed in the Jakarta Islamic Index on the Stock Exchange in the year 2008-2012. Samples were taken by using purposive sampling method and sample selection criteria. The samples used were 38 companies. Based on the results of tests performed by t test NPM and INTO variables significantly influence variable CSR disclosure. While going through the t test can be seen that the variable ROA, CR, and DER no significant effect on CSR disclosure. While based on simultaneous test (F test) ROA, NPM, CR, DER, and INTO simultaneously having an influence on CSR disclosure. R2 is the magnitude of 0.206. This suggests that the major effect of the independent variables are ROA, NPM, CR, DER and INTO the dependent variable is CSR disclosure can be explained by the model equations by 20.6% while the remaining 79.4% is influenced by other factors beyond research.